Associate Degree in the Caribbean with particular reference to the OECS - Peters, Bevis ...[et al.] (UWI TLI Unit Cave HillBB, 2002)
Looks at the emergence of the Associate Degree in the United States and gives an overview of the different types of Associate Degrees that have evolved in the Caribbean. Reviews the development of a framework for the Associate Degree for the OECS. Identifies and examines some imported initiatives which should contribute to the long-term viability of the Associate Degree in the sub-region.